2022
DOI: 10.3171/2022.3.peds21512
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in pediatric hydrocephalus patients treated with endoscopic third ventriculostomy and choroid plexus cauterization: a systematic review and meta-analysis

Abstract: OBJECTIVE Endoscopic third ventriculostomy and choroid plexus cauterization (ETV+CPC) is a novel procedure for infant hydrocephalus that was developed in sub-Saharan Africa to mitigate the risks associated with permanent implanted shunt hardware. This study summarizes the hydrocephalus literature surrounding the ETV+CPC intraoperative abandonment rate, perioperative mortality rate, cerebrospinal fluid infection rate, and failure rate. METHODS This systematic review and meta-analysis followed a prespecified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This complication is one of the more serious complications of ETV. Fukuhara et al identified central nervous system infection as an independent risk factor for ETV failure [28,58,59]. Despite the occurrence of infection, the prognosis is significantly better than that of patients with infection after shunt surgery, and in most cases, the infection can be controlled with targeted medical therapy [28,29,59].…”
Section: Cerebrospinal Fluid Leakagementioning
confidence: 99%
“…This complication is one of the more serious complications of ETV. Fukuhara et al identified central nervous system infection as an independent risk factor for ETV failure [28,58,59]. Despite the occurrence of infection, the prognosis is significantly better than that of patients with infection after shunt surgery, and in most cases, the infection can be controlled with targeted medical therapy [28,29,59].…”
Section: Cerebrospinal Fluid Leakagementioning
confidence: 99%
“…As such, the practice and outcomes of these techniques in LMICs warrant systematic review and meta-analysis. Previous work has examined the management and outcomes of hydrocephalus in HICs and LMICs13 14 although in unstratified medical subject headings age groups and aetiologies.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the practice and outcomes of these techniques in LMICs warrant systematic review and meta-analysis. Previous work has examined the management and outcomes of hydrocephalus in HICs and LMICs (13, 14) albeit in unstratified medical subject headings (MeSH) age groups and aetiologies.…”
Section: Introductionmentioning
confidence: 99%